The Servant Leadership of Administrator and the Quality of Work Life of Teacher in School Under the Office of Phetchaburi Primary Educational Service Area 2 - Maliwong, Wychayanee; Inrak, Sangaun; Chenaksara, Nopadol; Tiacharoen, Saisuda (Journal of Dhamma for Life, 2025)
The purposes of this research were to determine; 1) the servant leadership of administrators in schools under the office of Phetchaburi Primary Educational Service Area 2, 2) the quality of work life of teacher in school under the office of Phetchaburi Primary Educational Service Area 2, and 3) the relationship between the servant leadership of school administrator and quality of work life of teacher under the office of Phetchaburi Primary Educational Service Area 2. The sample of this research were 97 schools under the office of Phetchaburi Primary Educational Service Area 2. The respondents in each school consisted of 2 persons; school director and teacher with the total of 194. The research instrument was an opinionnaire regarding the servant leadership of school administrator based on the concept of Greenleaf and the quality of work life of teacher based on the concept of Walton. The statistics used for data analysis were frequency, percentage, arithmetic mean, standard deviation and Pearson’s product moment correlation coefficient. The findings revealed as follows; 1) the servant leadership of school under the office of Phetchaburi Primary Educational Service Area 2 as a whole and as an individual, was at a high level. The arithmetic mean ranking from the highest to the lowest were as follows, commitment of the growth of people, building community, persuasion, conceptualizing, stewardship, awareness, foresight, acceptance and empathy, healing, and listening. 2) The quality of work life of teacher under the office of Phetchaburi Primary Educational Service Area 2 as a whole and as an individual, was at a high level. The arithmetic mean ranking from the highest to the lowest were as follows, immediate opportunity to use develop human capacities, social integration in the work organization, constitutionalism in to the work organization, future opportunity for continued growth and security, social relevance of work life, safe and healthy working condition, work and the total life space, and adequate and fair compensation. 3) There was significant relationship between the servant leadership of school administrator and quality of work life of teacher under the office of Phetchaburi Primary Educational Service Area 2 at .01 significant level.